PERANCANGAN TAMBAL BAN MENGGUNAKAN ELEKTRIK DI TEMBILAHAN - SLAMET RIYADI (Program Studi Teknik Industri, 2018)
This design is a type of development design that aims to produce a media tire penampal tool that uses electrical system that is economical and practical as a business and know the feasibility of the product in the form of tire penampal that uses electrical system this tool to penampal motorcycle ynag heating using electricity does not use fire The excess of this design can be useful for the community does not pose a danger to the community and also for students to know the development of technology still play a very important role in the era of take-off as it is today, and we are demanded to be able to display a product with a decent quality and Can be accountable for the truth. Especially in small business (Home industry) government give impetus in order to improve product that yielded both in terms of quality and quantity.